Public Perception of Electric Cigarettes Based Health Knowledge Level in Palembang - Siti Farahhiyah Dwi Mubarani (Community Medicine and Education Journal, 2020)
The Nicotine Replacement Therapy (NRT) method is a medium for giving nicotine needed by smokers without burning tobacco. An electric cigarette is one from many NRTs that uses electricity from battery power to deliver nicotine in the form of vapor. But it is not recommended by the WHO or the Food and Drug Administration (FDA) because it has many negative effects. According to Green, there are 3 behavioral factors which are predisposition, support and drive. According to Notoatmodjo, lack of knowledge can form a false perception of electric cigarettes. According to Hude, perception is the giving of meaning to the stimulus received by sensory systems. The purpose of this research is to know the relation of demographic characteristic and to identify health knowledge to know public perception about the existence of electric cigarette in Palembang City. This research is a quantitative analytical research with cross sectional study design conducted in Palembang city using questionnaire in February 2018. The sample of this research is male active smoker with age> 15 years in Palembang city taken by purposive sampling technique. The data obtained were analyzed by univariate analysis, chi square test, and multivariate logistic regression analysis using IBM SPSS statistic version 22. The study obtained 162 respondents who met the inclusion criteria. The result of statistical test in this research is 51.2% positive perception toward electric cigarette based on health knowledge level in Palembang city (p = 0,000). There is no significant relationship between demographic characteristics and public perception of electric cigarette (p> 0,005). Predisposing factors concerning knowledge of electric cigarette usage can cause addiction problem is the most dominant factor in shaping people's perception on electric cigarette (p = 0,008).